PENENTUAN HARGA POKOK PENJUALAN USAHA PENGGEMUKAN SAPI POTONG MITRA DAN NON-MITRA DI DESA ASTOMULYO KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Novalia Novalia; Raden Hanung Ismono; Adia Nugraha (Lampung University, 2021)
This research aims to find out production main cost, selling main cost, and the differences of production main cost and selling main cost between partner and non-partner cattle fattening business. Furthermore, this research uses cencus method which is conducted on cattle fattening in Astomulyo Village, Punggur Subdistrict, Central Lampung Regency. The location are chosen purposively as the consideration that the Punggur Sub-district, Central Lampung Regency has the largest cattle population in Lampung Province. Data in this research are analyzed using production main cost, selling main cost and independent sample test. The result shows that: the production main cost of cattle fattening partner and non-partner is Rp39,119.17/kg and Rp40,552.24/kg, respectively. Then, the selling main cost of cattle fattening partner and non-partner is Rp39,763.90/kg and Rp40,736.12/kg, respectively. Finally, there is a significant difference in the production main cost and the selling main cost between partner and non-partner cattle fattening business.Key words: cattle fattening, production main cost, selling main cost